2016
DOI: 10.1186/s12906-016-1372-x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the impact of herb-drug combinations used by cancer patients

Abstract: BackgroundHerb/Dietary Supplements (HDS) are the most popular Complementary and Alternative Medicine (CAM) modality used by cancer patients and the only type which involves the ingestion of substances which may interfere with the efficacy and safety of conventional medicines. This study aimed to assess the level of use of HDS in cancer patients undergoing treatment in the UK, and their perceptions of their effects, using 127 case histories of patients who were taking HDS. Previous studies have evaluated the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
40
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 29 publications
7
40
0
3
Order By: Relevance
“…Doctors, in contrast to the patients, are aware of the possibility of adverse effects with simultaneous use of synthetic drugs and herbal preparations. 14,20 In the present study, it was shown that most of the respondents (68.5%) informed the doctor about taking herbal preparations. This is a large percentage compared to the results of other surveys, in which only one fourth of patients informed the doctor about simultaneous use of synthetic drugs and herbal products.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Doctors, in contrast to the patients, are aware of the possibility of adverse effects with simultaneous use of synthetic drugs and herbal preparations. 14,20 In the present study, it was shown that most of the respondents (68.5%) informed the doctor about taking herbal preparations. This is a large percentage compared to the results of other surveys, in which only one fourth of patients informed the doctor about simultaneous use of synthetic drugs and herbal products.…”
Section: Discussionmentioning
confidence: 55%
“…13 Research by Alsanad et al, conducted in the UK, indicate that adult cancer patients use herbal preparations (3.1% -21.8%) simultaneously with pharmacotherapy. 7,14 In less developed countries a higher percentage of patients use herbal OTC drugs or dietary supplements, e.g. in Palestine 69.5%, Malaysia 70.2%, and Ethiopia 79% .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been conducted to evaluate the safety of herbal medicines and their combinations used as self-medication, or as recommended by herbal medicine practitioners. 34 Fortunately, although HDIs instructions for many Traditional Chinese Medicines (TCMs) are not identified as "well-documented," some chemical drugs list the potential HDIs in the pharmaceutical directions. In addition, the potential for interactions between TCMs and chemical drugs needs to be revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Nutraceutical use is widespread but more prevalent in certain patient groups-the elderly, cancer sufferers, athletes and those trying to lose weight (Alsanad, Howard, & Williamson, 2016;Agbabiaka, Wider, Watson, & Goodman, 2017;Gurley et al, 2018). Many are taking conventional medicines at the same time and the possibility of drug interactions must be considered (Izzo, Hoon-Kim, Radhakrishnan, & Williamson, 2016;Awortwe, 2017).…”
mentioning
confidence: 99%
“…Many are taking conventional medicines at the same time and the possibility of drug interactions must be considered (Izzo, Hoon-Kim, Radhakrishnan, & Williamson, 2016;Awortwe, 2017). In the United Kingdom, Alsanad et al (2016) found a high use (34%) of health supplements in cancer patients. The most popular products taken showed a low potential for drug interaction and few patients reported any adverse events.…”
mentioning
confidence: 99%